Vibration-based condition assessment of a steel structure under ambient excitation - Kumar, Deepak; Lakshmi, K.; Srinivas, V.; Srinivas, A. (Journal of Structural Engineering, 2024)
Most of civil structures deteriorate with time due to many factors such as ageing, repeated loadings, wear-and-tear, lack of maintenance, and other environmental influences. While the structures are designed for strength, stability and deformation, the issues that are common are those of deterioration, durability and serviceability. Therefore, it is essential to assess the condition of the structures periodically if not continuously to prevent the deterioration leading to the decline of the strength, stability/serviceability. In real practice, the condition of structures is evaluated through condition assessment procedures. To evaluate the deterioration due to loss of stiffness, acceleration measurement which reflects the global information, is a great option when compared to strain, which needs a greater number of strain gages to capture the local information of a structure. In this paper, a method to evaluate the condition of a structure using acceleration responses is presented. The proposed technique is illustrated through an example of a steel building subjected to ambient excitations due to the operation of machinery. The technique is based on the updating of the Finite Element (FE) model of the structure, using the frequencies obtained from the measured acceleration response from the field. The frequencies obtained from the Modal analysis of the FE model are compared with the frequencies obtained from the field measurement. The dominant frequencies, excited with higher amplitudes in the field are found to be nearer to the FE frequencies but not the same. One of the main reasons for the difference is the change in the actual stiffness due to the deterioration of the member. This change or loss of stiffness is captured by updating the model with the frequencies of the field measured signal. Once the loss of stiffness is assessed, the current load-carrying capacity corresponding to the updated model is evaluated. The results of the studies from the steel building indicate the feasibility of the vibration-based technique for condition assessment. The proposed technique is able to identify the stiffness loss due to a reduction of the thickness of the column members by 9%, which is also verified using an ultrasonic thickness gauge in the field.